Analysis of The Influence of Facilities, Learning Environment, and Location on The Decision to Choose The Faculty Of Medicine, Universitas Ciputra - Indri Reswari Mustika Peni (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to determine the effect of facilities, learning environment, and location on the decision to choose the Faculty of Medicine, University of Ciputra. The population in this study were 300xx medical students at Ciputra University. While the sample used amounted to 104 respondents with the sampling method is simple random sampling Based on the results of the analysis carried out using the multiple linear regression method, it can be seen that the learning environment factors and location factors have a significant effect on the decision to choose medical students in choosing the Faculty of Medicine, Ciputra University.